Tackling anxiety in primary mathematics teachers - Wicks, Karen (Critical guides for teacher educators., 2021)
Provides teacher educators with an understanding of the issues around mathematics anxiety and a framework of teaching strategies to support trainees and teachers in primary settings in developing confidence in learning and teaching mathematics.